Konseling Kelompok dengan Teknik Behavioral untuk Meningkatkan Minat Belajar pada Siswa Slow Learner di Sekolah Dasar - Amelia Atika; Novi Andriati (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The problem in this research is that it is limited to the group counseling model to increase interest in learning in slow learner students, while the aim is to describe the description of interest in learning and the effectiveness of the group counseling model with behavioral techniques to increase student interest in learning. The method used in this research is qualitative descriptive research, data is obtained from interviews and observations as well as documentation to be described to describe the reality in the field. The research results show that students have done their schoolwork, focused on studying, can control their emotions, are responsible for the tasks given by the teacher and can socialize with their peers. The feasibility test results show that the designed model is suitable for implementation in the field. It can be concluded that the group counseling model using behavioral techniques can effectively increase interest in learning among slow learner students in all indicators which include: being responsible for the tasks given by the teacher, being disciplined in going to school, being active in learning activities in class and diligently doing homework.